Intervensi Focus Group Discussion (Fgd) dalam Meningkatkan Self Efficacy untuk Tidak Merokok pada Siswa SMK Ignatius Slamet Riyadi Surakarta - Risnanditiar Hirsya Priambodo; Budi Prasetyo; Dzul Fahmi Afriyanto (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Smoking becomes a common phenomenon among teenagers because due to internal and external factors affecting smoking behavior. Efficacy of self, confidence of one of his abilities, affects the smoking habits and efforts to stop. FGD (Focus Group Discussion) is an effective method of collecting information and troubleshooting through group discussions. FGD can increase the knowledge and efficacy of the participants' sourcing, including students at school. This study aims to determine how health promotion interventions can cultivate self effecty so that teens still do not smoke using the health promotion intervention method of FGD (Focus Group Discussion) and to know the success of self efficacy based on 3 aspects: (Level, Strenght, and Generality). This research uses a Quasi Experimental method with a type of quantitative research that uses a pre-test group post-test approach. The sample in this study were 10 students in class X and XI from SMK Igntaius Slamet Riyadi Surakarta. The sampling technique uses a purposive sampling method. Data collection techniques use interviews. The data analysis technique uses the non-parametric Wilcoxon Signed Ranks Test. The results of this study show that there is no influence of self-efficacy on the behavior of maintaining not smoking among students at SMK Igntaius Slamet Riyadi Surakarta. Indicates because there is no influence between the FGD variable and the self efficacy of maintaining behavior to remain non-smoking.